2002
DOI: 10.3138/jcfs.33.2.179
|View full text |Cite
|
Sign up to set email alerts
|

Who Interracially Dates: An Examination of the Characteristics of those who have Interracially Dated

Abstract: Interracial romantic relationships are a useful barometer of macrolevel race relations. Much of the research of who enters into interracial relationships concentrates upon marital relationships. While this research is useful, there is little research regarding who interracially dates. Logistical regression analysis was conducted on data from a telephone survey. European-Americans, African-Americans, Hispanic-Americans and Asian-Americans were analyzed separately. Similar demographic and social factors predicte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
94
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(100 citation statements)
references
References 0 publications
4
94
2
Order By: Relevance
“…Specifically, a one unit increase in residences lived at between waves is associated with a 5% increase in the odds of interracial relationship involvement (p \ .001). Finally, in contrast to prior research that has found that women are less likely to have dated interracially than men (Yancey 2002), gender is not a Race Soc Probl (2010) 2:92-100 97 significant predictor of interracial relationship involvement in this analysis. Despite the non-significance of the gender coefficient, the direction of the coefficient does support prior research.…”
Section: Resultscontrasting
confidence: 72%
See 4 more Smart Citations
“…Specifically, a one unit increase in residences lived at between waves is associated with a 5% increase in the odds of interracial relationship involvement (p \ .001). Finally, in contrast to prior research that has found that women are less likely to have dated interracially than men (Yancey 2002), gender is not a Race Soc Probl (2010) 2:92-100 97 significant predictor of interracial relationship involvement in this analysis. Despite the non-significance of the gender coefficient, the direction of the coefficient does support prior research.…”
Section: Resultscontrasting
confidence: 72%
“…For example, college-educated individuals are more likely to form interracial romantic unions and to marry interracially than their non-college educated counterparts (Lichter and Qian 2004;Yancey 2002). This pattern may be due to college-educated individuals having greater contact with individuals of different races/ethnicities (Powers and Ellison 1995), or alternatively may be explained by the more positive attitudes toward interracial relationship involvement that are generally noted among those with a higher education (Bobo 2001).…”
Section: Individual-level Characteristics Predicting Interracial Relamentioning
confidence: 91%
See 3 more Smart Citations